2014
DOI: 10.1007/8904_2014_316
|View full text |Cite
|
Sign up to set email alerts
|

Laronidase Replacement Therapy and Left Ventricular Function in Mucopolysaccharidosis I

Abstract: We assessed the effects of long-term laronidase replacement therapy (LRT) on the left ventricular (LV) function of a 52-year-old adult woman with mucopolysaccharidosis I (MPS I). The urinary uronic acid concentration significantly decreased by 78.7% (from 75 to 16 mg/g creatinine) after LRT; thereafter, estimated LV weight as assessed by two-dimensional (2D) echocardiography significantly decreased by 33.3% (from 189 to 126 g). Although systolic LV function of the ejection fraction as assessed by 2D echocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The recombinant enzyme is given intravenously at weekly intervals (Wraith, 2005). Studies have shown that ERT improves cardiac function (Harada et al, 2011(Harada et al, , 2014, respiratory function (Wraith, 2005), and range of motion (Tylki-Szymanska et al, 2010), and is most effective at halting or slowing disease progression if started before the onset of irreversible damage (Muenzer, 2014).…”
Section: Background Informationmentioning
confidence: 99%
“…The recombinant enzyme is given intravenously at weekly intervals (Wraith, 2005). Studies have shown that ERT improves cardiac function (Harada et al, 2011(Harada et al, , 2014, respiratory function (Wraith, 2005), and range of motion (Tylki-Szymanska et al, 2010), and is most effective at halting or slowing disease progression if started before the onset of irreversible damage (Muenzer, 2014).…”
Section: Background Informationmentioning
confidence: 99%